2007
DOI: 10.1038/sj.gt.3303036
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative study on the immunotherapeutic efficacy of recombinant Semliki Forest virus and adenovirus vector systems in a murine model for cervical cancer

Abstract: Currently, various therapeutic strategies are being explored as a potential means to immunize against metastatic malignant cells or even primary tumours. Using recombinant viral vectors systems or protein-based immunization approaches, we are developing immunotherapeutic strategies against cervical cancer or premalignant cervical disease, as induced by high-risk type human papillomaviruses (HPVs). We previously demonstrated that immunization of mice with recombinant replication-defective Semliki Forest virus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…The rSFV replicon particles encode a fusion protein of E6 and E7 derived from the most prevalent HPV type, HPV type 16 (SFVeE6,7) . We have successfully shown that immunization with SFVeE6,7 particles induces strong HPV‐specific cellular responses and eradication of established HPV‐transformed tumors …”
mentioning
confidence: 99%
“…The rSFV replicon particles encode a fusion protein of E6 and E7 derived from the most prevalent HPV type, HPV type 16 (SFVeE6,7) . We have successfully shown that immunization with SFVeE6,7 particles induces strong HPV‐specific cellular responses and eradication of established HPV‐transformed tumors …”
mentioning
confidence: 99%
“…Moreover, the transient nature of high level recombinant protein expression and rapid RNA replication with no risk of genome integration, are additional features making alphavirus vectors attractive. In relation to other viral vectors, 100–1000-fold lower doses of SFV were needed to elicit therapeutic efficacy of HPV E6-E7 immunization in comparison to vaccination with adenovirus vectors [107]. The tumor-targeting property of oncolytic alphaviruses has offered enhanced tumor growth inhibition and tumor eradication.…”
Section: Discussionmentioning
confidence: 99%
“…A comparative study between the prime-boosting efficacy of SFVeE6,7 and that of the recombinant adenovirus type 5 vector expressing the same antigen construct (Ad-eE6,7) revealed that SFVeE6,7 vaccination lead to higher precursor CTL frequencies and activity when compared to Ad-eE6,7 vaccination. The efficacy of SFVeE6,7 vaccination in murine tumor treatment experiments was significantly higher than that of the Ad-eE6,7 counterpart [172]. Also, low doses of IL-12 expressed by a SFV virus vector (SFV-IL12) augmented the antigen-specific and antitumor responses induced by the virus vector alone [173].…”
Section: Shifting the Balance: Strategies To Improve Homing And Acmentioning
confidence: 99%